Mechanisms underlying the vasorelaxant effect of hydrogen sulfide on human saphenous vein. (11th March 2021) - Marinko, Marija; Hou, Hai‐Tao; Stojanovic, Ivan; Milojevic, Predrag; Nenezic, Dragoslav; Kanjuh, Vladimir; Yang, Qin; He, Guo‐Wei; Novakovic, Aleksandra
Abstract: Hydrogen sulfide (H2 S) represents the third and the youngest member of the gaseous transmitters family. The dominant effect of H2 S on isolated vessels is vasodilation. As the mechanism of H2 S‐induced relaxation in human vessels remains unclear, the present study aimed to investigate the effects of H2 S donor, sodium hydrosulfide (NaHS), on isolated human saphenous vein (HSV) and to determine the mechanism of action. Our results showed that NaHS (1 µM–3 mM) induced a concentration‐dependent relaxation of endothelium‐intact HSV rings pre‐contracted by phenylephrine. Pre‐treatment with L‐NAME, ODQ and KT5823 significantly inhibited NaHS‐induced relaxation, while indomethacin induced partial inhibition. Among K + channel blockers, the combination of apamin and TRAM‐34 significantly affected the relaxation produced by NaHS, while iberiotoxin and glibenclamide only reduced maximal relaxation of HSV. NaHS partially relaxed endothelium‐intact rings pre‐contracted by high K +, as well as phenylephrine‐contracted rings in the presence of nifedipine. Additionally, the incubation of HSV rings with NaHS increased NO production. These results demonstrate that NaHS produces the concentration‐ and endothelium‐dependent relaxation of isolated HSV. Vasorelaxation to NaHS probably involves activation of NO/cGMP/PKG pathway and partially prostacyclin. In addition, different K + channels subtypes, especially SKCa and IKCa, as well as BKCa and KATP channels in high concentrations of NaHS, probably participate in the NaHS‐induced vasorelaxation.